Longitudinal 18F-VUIIS1008 PET imaging in a rat model of rheumatoid arthritis - Su, Xinhui; Wang, Liangliang; Yang, Rongshui; Guo, Zhide (Frontiers in Chemistry, 2022)
Macrophages have crucial roles in the pathogenesis of rheumatoid arthritis (RA). We aimed to elucidate the temporal profile of macrophage infiltration in synovitis in RA rat models using PET (positron emission tomography) imaging based a new generation of TSPO (Translocator protein, 18 kDa)-PET ligand, 18F-VUIIS1008 [2-(5,7-Diethyl-2-(4-(2-[18F]fluoroethoxy)phenyl)pyrazolo[1,5-a]pyri-midin-3-yl)-N, N-diethylacetamide]. In vitro and in vivo studies were conducted using RAW264.7 macrophage cells and a rat model of RA induced by Complete Freund’s Adjuvant (CFA). Our results showed 18F-VUIIS1008 showed excellent stability in vitro and binding specificity to RAW264.7 cells, and rapid accumulation in the left inflammatory ankles. PET studies revealed that 18F-VUIIS1008 could clearly identify the left inflammatory ankles with good contrast at 30-120 min post-injection. The uptake of 18F-VUIIS1008 of left inflammatory ankles was a wiggle trace with two peaks on day 7 and 29, and then, the highest peak uptake was seen on day 29 (3.00 ± 0.08 %ID/g) at 60 min after injection. Tracer uptakes could be inhibited by PK11195 or VUIIS1008. Immunohistochemistry and immunofluorescence tests showed that elevated TSPO expression and infiltrated macrophages were found in the left inflammation ankles. 18F-VUIIS1008 as a novel PET imaging agent showed great potential to identify temporal profile of macrophage infiltration in synovitis in RA, and deliver accurate non-invasive diagnosis and real-time monitoring of RA development.